2018
DOI: 10.1097/jcn.0000000000000415
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nurse Staffing on In-Hospital Mortality of Stroke Patients in Korea

Abstract: Policies to educate sufficient numbers of nurses and retain them in the field are warranted, especially because medical-cost containment has become a dominant concern in most countries. Further studies are needed to understand the mechanisms and other protective roles of nurse staffing to ensure long-term health outcomes after hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 24 publications
1
27
1
Order By: Relevance
“…In terms of type of insurance, the 30-day post-discharge mortality risk was highest in Medical Aid dependents and was lowest in workers who paid for National Health Insurance themselves. This is in accordance with previous findings that the ORs for unplanned readmission under Medicaid for some people with limited income and resources were higher than those of patients who received health coverage from health maintenance organizations in the USA [2] and that the ORs for in-hospital mortality among stroke patients with Medical Aid were higher for some people with limited income and resources in Korea [10]. Based on these findings, participants' engagement in economic activities and social characteristics can be inferred to have a significant influence on post-discharge mortality and in-hospital mortality.…”
Section: Hospital and Patient Characteristics And 30-day Postdischargsupporting
confidence: 93%
See 1 more Smart Citation
“…In terms of type of insurance, the 30-day post-discharge mortality risk was highest in Medical Aid dependents and was lowest in workers who paid for National Health Insurance themselves. This is in accordance with previous findings that the ORs for unplanned readmission under Medicaid for some people with limited income and resources were higher than those of patients who received health coverage from health maintenance organizations in the USA [2] and that the ORs for in-hospital mortality among stroke patients with Medical Aid were higher for some people with limited income and resources in Korea [10]. Based on these findings, participants' engagement in economic activities and social characteristics can be inferred to have a significant influence on post-discharge mortality and in-hospital mortality.…”
Section: Hospital and Patient Characteristics And 30-day Postdischargsupporting
confidence: 93%
“…Studies of the associations between inpatient or postdischarge patient mortality and nurse staffing for patients with various conditions-treated medically or surgically-have been conducted in many countries, and the likelihood of patient mortality has been found to be reduced by increased nurse staffing in several settings, including general wards, emergency departments, and intensive care units (ICU) [5][6][7][8]. Furthermore, in a Korean study of patients with diseases such as stroke and cardiovascular disease, it was found that in-hospital or 30-day mortality had statistically significant associations with the nurse staffing level [9][10][11]. Although many studies have investigated these patient outcomes, less research has investigated cases where patients die in the community setting, such as at home or a nursing home without appropriate safeguards, due to a health problem that occurred after they were discharged post-surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the staffing of nurses was related to mortality, incidence of falls, length of hospital stay, and medication errors [11]. Chung and Sohn [12] studied the relationship between the staffing of nurses and in-hospital mortality of stroke patients in 615 hospitals in South Korea. The results showed that the staffing of nurses was a barrier factor in the mortality of stroke patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…Chung and Sohn [12] studied the relationship between the staffing of nurses and in-hospital mortality of stroke patients in 615 hospitals in South Korea. The results showed that the staffing of nurses was a barrier factor in the mortality of stroke patients [12]. Zhu et al [13] analysed the relationship between the staffing of nurses and patient outcomes in 181 hospitals in China.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our data, the overall PBR in rural hospitals is 1:11.1, and the overall NBR is 1:13.6, which is significantly lower compared with most hospitals in urban areas of China and other developed countries [7][8][9]. Heavy workload directly causes fatigue, which is associated with increased medical errors [10,11].…”
Section: Discussionmentioning
confidence: 83%